Examination of Suitable Bandgap Grading of Cu(InGa)Se2 Bottom Absorber Layers for Tandem Cell Application. Issue 10 (12th March 2021) - Jeong, Changwook; Nagai, Takehiko; Ishizuka, Shogo; Tampo, Hitoshi; Hajime, Shibata; Kim, Shinho; Kim, Yangdo
Abstract : A high‐efficiency tandem solar cell comprises of top and bottom solar cells. The bottom cell has a bandgap of ≈1.1 eV and is designed to absorb longer wavelengths of photons. A Cu(InGa)Se2 (CIGS) is one of the candidates for a bottom solar cell, but its bandgap is not constant and is graded with depth. This study discusses suitable bandgap grading of CIGS cells for bottom cell applications. Three CIGS devices with different bandgap gradings are prepared for bottom cell evaluation. One device has a single‐back‐graded bandgap type whereas the others have double‐graded bandgap types, which have been used for high‐efficiency CIGS devices. The three CIGS devices exhibit similar conversion efficiencies of ≈20% but different solar cell parameters, due to their different shapes of bandgap grading. For the bottom cell evaluations, current–voltage measurements are performed using 720 nm (≈1.72 eV) and 800 nm (≈1.55 eV) long‐pass filters. It is found that a CIGS device with a double‐graded bandgap is unsuitable and/or shows reduced performance with a decreased top cell bandgap. By contrast, CIGS devices with a single‐back‐graded bandgap can be adopted as a bottom cell under top cell bandgaps of both ≈1.55 and ≈1.72 eV. Abstract : It is found that a Cu(InGa)Se2 (CIGS) device with a double‐graded bandgap is unsuitable and/or shows reduced performance with a decreased top cell bandgap. By contrast, CIGS devices with a single‐back‐graded bandgap can be adopted as a bottom cell under top cell bandgaps of both ≈1.55 and ≈1.72 eV.